2017
DOI: 10.1039/c7ra02019h
|View full text |Cite
|
Sign up to set email alerts
|

Europium complexes: choice of efficient synthetic routes from RM1 thermodynamic quantities as figures of merit

Abstract: Faced with many different plausible synthetic pathways for the preparation of europium complexes, the synthetic chemist can now easily compute RM1 thermodynamic quantities for all of them and likely arrive at the most effective synthetic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…For this purpose, we adapted the conventional synthesis previously reported in detail for ternary complexes. Accordingly, the reaction was performed in four steps in a one-pot procedure. In parallel, we also performed a microwave-assisted route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we adapted the conventional synthesis previously reported in detail for ternary complexes. Accordingly, the reaction was performed in four steps in a one-pot procedure. In parallel, we also performed a microwave-assisted route.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure followed the ionic ligand addition order that was previously established: DBM > NTA > BTFA > TTA . A KOH ethanolic solution (0.4 mmol) was added slowly to 2 mmol of HDBM dissolved in ethanol (5 mL), under constant stirring for 30 min.…”
Section: Methods and Experimental Sectionmentioning
confidence: 99%
“…Previously, our research group reported a strategy for the synthesis of mixed-ligand europium complexes with chloride and β-diketonate ligands, exemplified by the synthesis of [EuCl 2 (TTA)(TPPO) 3 ] from [EuCl 2 (TPPO) 4 ]Cl·3H 2 O. 21 This same strategy was followed for the syntheses of all five novel complexes [EuCl 2 (BTFA)(TPPO) 3 ], [EuCl(TTA) 2 (TPPO) 2 ], [EuCl(BTFA) 2 (TPPO) 2 ], [EuCl(DBM) 2 (TPPO) 2 ], and [EuCl(DBM)(TTA)(TPPO) 2 ], all starting from 1 mmol of [EuCl 2 (TPPO) 4 ]Cl·3H 2 O as well. In all cases, after the first addition of 1 equiv of a ligand, we let the mixture sit under reflux for 16 h and after the addition of another equivalent of either the same ligand or of another ligand, we let the mixture sit under stirring and reflux for 24 more hours.…”
Section: Experimental Section and Computational Methodsmentioning
confidence: 99%
“…For this purpose, we synthesized five novel chloride complexes: [EuCl 2 (BTFA)(TPPO) 3 ]; [EuCl(TTA) 2 (TPPO) 2 ]; [EuCl(BTFA) 2 (TPPO) 2 ]; [EuCl(DBM) 2 (TPPO) 2 ]; and [EuCl(DBM)(TTA)(TPPO) 2 ]. We also measured in this article the luminescence properties of five other chloride complexes that had syntheses and characterizations recently reported by our research group: [EuCl 2 (TPPO) 4 ]Cl·3H 2 O, 20 [EuCl 2 (TTA)(TPPO) 3 ], 21 [EuCl 2 (DBM)(TPPO) 3 ], 21 [EuCl 2 (TTA)(BTFA)(TPPO) 3 ], 21 and [EuCl 2 (DBM)(BTFA)(TPPO) 3 ]. 21 Finally, to complete the luminescence databank for the combinatorial set of compounds, we included the previously determined luminescence properties of ternary europium(III) complexes of the types [Eu(β) 3 (TPPO) 2 ], 14,22,23 [Eu(β) 2 (β′)(TPPO) 2 ], 19 and [Eu(β)(β′)(β″)(TPPO) 2 ], 19 where β ≠ β′ ≠ β″ can be either 1-(2-thenoyl)-3,3,3-trifluoroacetone (TTA), 4,4,4-trifluoro-1-phenyl-1,3-butanedione (BTFA), or 1,3-diphenylpropane-1,3-dione (DBM).…”
Section: Introductionmentioning
confidence: 99%
“…The energy is transferred to the Eu 3+ cation, which emits luminescence with high intensity. On the other hand, two water molecules can be relatively easily exchanged for some components of the LFM, 32 changing the luminescent properties of the complex. 33 The luminescent property of the complex has been utilized to visualize LFM on porous surfaces with an enhanced signal-to-background ratio.…”
mentioning
confidence: 99%